Menyoal Kembali Teori Evolusi Agama J.G. Frazer dalam Keberagamaan Masyarakat Jawa - Muhammad Rikza Muqtada (Institut Agama Islam Negeri (IAIN) Salatiga, 2016)
Religion is seen as the result of philosophers’ thinking production which has a tendency to solve the riddle of life and to spread their ideas and their thoughts to others. Frazer is one pushed for discovering when the religion began to exist. The conclusion is that the human belief system, in accordance with a level of reasoning ability, evolves from magical belief, than religous belief, and ends on science. Nevertheless, when it is compared to the religious phenomenon in Indonesia, especially in Java, Frazer’s theory is not entirely true and debatable. The religious system in Java exactly does not have evolution as interpreted in Frazer’s theory. With its elasticity, genuine Javanese belief – dynamism and animism – only underwent assimilation with foreign cultures that came later like Islam and Christian, and including Western culture. In the context of Javanese religiosity, those three beliefs system as intended by Frazer, take place integrally and parallel in modern Javanese culture.